American and Chinese Thinking Styles: Attitude Effects on Holistic and Attribute Ads - Liang, Beichen; Cherian, Joseph (Organizations and Markets in Emerging Economies, 2014)
American (i.e., Western) thinking favors the analytic style, focusing on the focal object and internal attributes; Chinese (i.e., Eastern) thinking favors the holistic style, paying attention to the context and whole system. This research investigates whether such holistic and analytic thinking styles affect attitudes towards holistic ads which contain many types of information (availability, price, company, etc.) and attribute ads which contain only one type of information (product feature). The first study showed that (i) American consumers prefer attribute ads more than Chinese consumers do; (ii) both American and Chinese consumers prefer holistic ads more than attribute ads; and both prefer the holistic ads equally well. The second study showed that the impact of cultural differences in thinking styles on ad attitudes were not influenced by thinking speed – whether the thinking was fast and automatic or whether the thinking was slow and effortful. The stable and verifiable managerial implication is that ad content in the East and West, in the US and China must include more, diverse information.
Keywords: ad information; analytic thinking; holistic thinking; culture; ad attitudes